Sizing of building water piping systems under real flow rate - Petrucci, Aron Lopes (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Most of the calculation techniques used for sizing building water piping systems does not assess the real flow and pressure that exist in each section of the pipe. When using such techniques, we can only verify the dynamic pressure agreement with given references for a given maximum flow rate. Therefore it is not possible to precisely determine how the operation of an appliance can influence another. This paper proposes a model for calculating the water consumption in buildings with open piping networks, under steady flow, which allows the real flow rate and pressure present in each point to be determined for any given use configuration. Every hydraulic law is determined for each component, as well as for each appliance attached to the piping. By using a numerical algorithm it is possible to determine flow rate and pressure values that satisfy all internal laws. This paper also presents considerations about a possible change of the paradigm used in building water systems sizing, from the traditional approach (that determines the maximum probable flow rate), to one in which the probability of occurrence of a given use configuration must be determined.